Substrate orientation effects on the nucleation and growth of the Mn+1AXn phase Ti2AlC - Tucker, Mark; Persson, P.; Guenette, M.; Rosén, J.; Bilek, M.; McKenzie, D. (American Institute of Physics, 2011)
The Mn+1AXn MAX phases are ternary compounds comprising alternating layers of a transitionmetal carbide or nitride and a third “A-group” element. The effect of substrate orientation on thegrowth of Ti2AlC MAX phase films was investigated by studying pulsed cathodic arc depositedsamples grown on sapphire cut along the 0001, 101¯0, and 11¯02 crystallographic planes.Characterization of these samples was by x-ray diffraction, atomic force microscopy, andcross-sectional transmission electron microscopy. On the 101¯0 substrate, tilted 101¯8 growth ofTi2AlC was found, such that the TiC octahedra of the MAX phase structure have the sameorientation as a spontaneously formed epitaxial TiC sublayer, preserving the typical TiC–Ti2AlCepitaxial relationship and confirming the importance of this relationship in determining MAX phasefilm orientation. An additional component of Ti2AlC with tilted fiber texture was observed in thissample; tilted fiber texture, or axiotaxy, has not previously been seen in MAX phase films.